Mozart, Sonata in D Major, K. 284, performed by Tomasz Ritter - Beghin, Tom (Ghent, Belgium Orpheus Institute, 2023)
As part of the 2023 Orpheus Historical Piano Summer Academy, Tomasz Ritter (Poland) performs Mozart’s Sonata in D Major, K. 284, on fortepiano (Stein, 1786, replica by Chris Maene, 2016) in the Koningssalon of D’Hane-Steenhuyse, Ghent, Belgium. This filmed performance is the result of a ten-day experimental workshop around the eighteenth-century practice of varying repeats; see also Mit veränderten Reprisen: The Practice of Varying Repeats, a film documentary by Tom Beghin (2023).
In the summer of 2023, a workshop was held at the Orpheus Institute, Ghent, Belgium, around the practice of varying repeats, directed by Tom Beghin, with guests Benjamin Steens and Juliane Brandes. Six young keyboardists from around the world gathered around the clavichord and fortepiano to familiarize themselves with CPE Bach’s unique opus of “Sonatas with Varied Reprises” (1760) as well as Mozart’s six early keyboard sonatas, K. 279–284 (1774–75). As today’s performers of classical keyboard sonatas, what happens when we submit ourselves to a once lively expectation of continuous variation? How do we navigate the materiality of a printed score? What are the limits of “writing in” our variants and at what point do we start over—indeed, create a new edition altogether?
FRIS
0
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850